A Home–School Partnership Model for Children's Foundational Competencies During School Transition - Agustini Agustini; Wenny Hulukati; Abd. Hamid Isa; Pupung Puspa Ardini (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2026)
This study aims to design, develop, implement, and evaluate a collaborative Home–School Partnership model to enhance children's foundational competencies during the transition from early childhood education to primary school in Gorontalo Province, Indonesia. Employing a research and development approach within the ADDIE framework (Analysis, Design, Development, Implementation, Evaluation), data were collected from parents of Grade I and II students across several elementary schools using questionnaires, observations, interviews, and focus group discussions. Model effectiveness was assessed through a pretest–posttest experimental design measuring changes in parental understanding and engagement. Results demonstrate high expert validity (91.72%) and strong practicality (93.14%) during small-group and large-group trials. Effectiveness evaluation revealed significant improvements in parental understanding, with posttest scores ranging from 79.70 to 84.20. Parents reported increased awareness of children's socio-emotional development, communication skills, independence, and positive learning attitudes beyond academic preparation. The study concludes that the Home–School Partnership model effectively strengthens parent–teacher collaboration and supports holistic child development during the transition to primary education. The novelty lies in its systematic development and validation of a structured partnership model specifically contextualized to the Indonesian educational landscape, addressing the critical yet underexplored transition period between early childhood and primary schooling. Practically, the model offers a replicable framework that can be integrated into school programs to foster sustainable home–school partnerships. This study contributes to educational literature by providing empirical evidence that structured family-school collaboration significantly enhances parental engagement and foundational competency development during a pivotal stage in children's educational trajectories.